The Relationship The Relationship between Genetic Factors and Clean and Healthy Living Behavior with the Incidence of Stunting in Toddlers at the Pagambiran Health Center in 2024 - Mia, Trya Mia Intani; Defi Yulita; Titin Ifayanti (Jurnal Amanah Kesehatan, 2025)
Stunting in children is one of the main public health problems in Indonesia. Data from the West Sumatra Provincial Health Office, the number of stunting reached 27.47%. risk factors for stunting include direct genetic factors and indirect clean and healthy living behavior. The purpose of this study was to determine the relationship between genetic factors and clean and healthy living behavior with the incidence of stunting in toddlers at the Pagambiran Health Center in 2024. This research method is Observational Analytical with a Cross Sectional approach. The study was conducted from March to August 2024 at the Pagambiran Health Center. The population of this study were all parents of toddlers at the Pagambiran Health Center. The sample of this study was mothers who had toddlers aged 24-59 months according to the inclusion and exclusion requirements of 30 respondents. The sampling technique was total sampling. Data collection used questionnaires and measuring the height of toddlers and the age of toddlers. Univariate and bivariate data analysis used the Chi square test. The results of the study found that 53.3% of toddlers experienced stunting, 66.7% more than half had genetic factors, 60% more than half of toddler families did not maintain clean and healthy living behaviors with the conclusion that there was a relationship between genetic factors and PHBS with the incidence of stunting at the Pagambiran Health Center. It is hoped that the role of midwives needs to be carried out in providing more comprehensive information so that the community can apply it in the family environment to prevent stunting.